Moss-cyanobacteria associations as biogenic sources of nitrogen in boreal forest ecosystems - Rousk, Kathrin; Jones, Davey L.; DeLuca, Thomas H. (Frontiers in Microbiology, 2013)
The biological fixation of atmospheric nitrogen (N) is a major pathway for available N entering ecosystems. In N-limited boreal forests, a significant amount of N2 is fixed by cyanobacteria living in association with mosses, contributing up to 50 % to the total N input. In this review, we synthesize reports on the drivers of N2 fixation in feather moss-cyanobacteria associations to gain a deeper understanding of their role for ecosystem-N-cycling. Nitrogen fixation in moss-cyanobacteria associations is inhibited by N inputs and therefore, significant fixation occurs only in low N-deposition areas. While it has been shown that artificial N additions in the laboratory as well as in the field inhibit N2 fixation in moss-cyanobacteria associations, the type, as well as the amounts of N that enters the system, affect N2 fixation differently. Another major driver of N2 fixation is the moisture status of the cyanobacteria-hosting moss, wherein moist conditions promote N2 fixation. Mosses experience large fluctuations in their hydrological status, undergoing significant natural drying and rewetting cycles over the course of only a few hours, especially in summer, which likely compromises the N input to the system via N2 fixation. Perhaps the most central question, however, that remains unanswered is the fate of the fixed N2 in mosses. The cyanobacteria are likely to leak N, but whether this N is transferred to the soil and if so, at which rates and timescales, is unknown. Despite our increasing understanding of the drivers of N2 fixation, the role moss-cyanobacteria associations play in ecosystem-N-cycling remains unresolved. Further, the relationship mosses and cyanobacteria share is unknown to date and warrants further investigation.